HLA-G: An Important Mediator of Maternal-Fetal Immune-Tolerance - Zhuang, Baimei; Shang, Jin; Yao, Yuanqing (Frontiers in Immunology, 2021)
HLA-G, one of the non-classical HLA class I molecules, is restricted-expression at extravillous trophoblast. It can concordantly interacts with various kinds of receptors mounted on maternally immune cells resided in uterus (e.g. CD4+ T cell, CD8+ T cell, natural killer cell, macrophage, dendritic cell) for maintaining immune homeostasis on maternal-fetus interface. HLA-G is widely regarded as the pivotal protective factor for successfully pregnancy. In the past 20 years, researches associated with HLA-G have been continually published. Indeed, HLA-G plays a mysterious strength in the mechanism of maternal-fetal immune-tolerance. It can also be ectopic expressed on tumor cells, infected site and suchlike pathologic microenvironment for conferring a significant local tolerance. To understand about the characteristic of HLA-G in immunologic tolerance is not only beneficial for pathological pregnancy, but also helpful to therapy of other immune-related disease, such as organ transplant rejection, tumor migration, and autoimmune disease. In this review, we describe the biological properties of HLA-G, then, summarize our understanding of mechanisms of fetomaternal immunologic tolerance and, moreover, the difference from transplant tolerance, Furthermore, we will discuss how HLA-G contribute to tolerogenic microenvironment during pregnancy. Finally, we hope to find some new aspect for HLA-G in fundamental research or clinical application for future.